Staged Correction of Severe Thoracic Kyphosis in Patients with Multilevel Osteoporotic Vertebral Compression Fractures. (November 2016) - Behrbalk, Eyal; Uri, Ofir; Folman, Yoram; Rickert, Marcus; Kaiser, Radek; Boszczyk, Bronek Maximilian
Study Design: Technical report. Objective: Multilevel osteoporotic vertebral compression fractures may lead to considerable thoracic deformity and sagittal imbalance, which may necessitate surgical intervention. Correction of advanced thoracic kyphosis in patients with severe osteoporosis remains challenging, with a high rate of failure. This study describes a surgical technique of staged vertebral augmentation with osteotomies for the treatment of advanced thoracic kyphosis in patients with osteoporotic multilevel vertebral compression fractures. Methods: Five patients (average age 62 ± 6 years) with multilevel osteoporotic vertebral compression fractures and severe symptomatic thoracic kyphosis underwent staged vertebral augmentation and surgical correction of their sagittal deformity. Clinical and radiographic outcomes were assessed retrospectively at a mean postoperative follow-up of 34 months. Results: Patients' self-reported back pain decreased from 7.2 ± 0.8 to 3.0 ± 0.7 (0 to 10 numerical scale; p < 0.001). Patients' back-related disability decreased from 60 ± 10% to 29 ± 10% (0 to 100% Oswestry Disability Index; p < 0.001). Thoracic kyphosis was corrected from 89 ± 5 degrees to 40 ± 4 degrees ( p < 0.001), and the sagittal vertical axis was corrected from 112 ± 83 mm to 38 ± 23 mm ( p = 0.058). One patient had cement leakage without subsequent neurologic deficit. Decreased blood pressure was observed in another patient during the cement injection. No correction loss, hardware failure, or neurologic deficiency was seen in the other patients. Conclusion: The surgical technique described here, despite its complexity, may offer a safe and effective method for the treatment of advanced thoracic kyphosis in patients with osteoporotic multilevel vertebral compression fractures.